Hundred Micro-Joules Level High Power Chirped Pulse Amplification of Femtosecond Laser Based on Single Crystal Fiber - Feng Li; Zhi Yang; Zhiguo Lv; Xiaohong Hu; Yufeng Wei; Qianglong Li; Shukuai Tang; Yishan Wang; Xiaojun Yang; Wei Zhao (IEEE Photonics Journal)
We demonstrate a hundred micro-Joules level femtosecond laser system based on a compact and simple two-stage Yb:YAG single crystal fiber chirped pulse amplification system which delivers compressed power of 15.57 W, pulse width of 715 fs. The different amplification performance with different input seed power is experimentally studied. A maximum direct amplified power output of 44 W at 100 kHz is obtained for an input seed power of 12 W. To the best of our knowledge, this is the highest average power of femtosecond laser based on single crystal fiber at hundred micro-Joules energy level.